2016
DOI: 10.2174/1567205013666160401114601
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol Reverse Hippocampal Neuron Cyclooxygenase-2 Downstream Signaling Imbalance in Aluminum-Overload Rats

Abstract: Although COX-2 inhibition in animal models of neurodegenerative diseases has shown neuroprotection, recent studies have revealed some serious side effects (ulcers, bleeding, fatal cerebrovascular diseases etc.) and the limited benefits of COX-2 inhibitors. A more focused approach is necessary to explore the therapeutic effect of the COX downstream signaling pathway in neurological research. The aim of this study was to explore the alterations of the PGES-PGE2-EP signal pathway and the effect of misoprostol on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…24,25 Our previous study showed that the four different receptor subtypes of PGE2 participated in brain injury caused by aluminum overload. 26 On the basis of these reports, we hypothesized that COX2 and its downstream signaling pathway may participate in cognitive impairment in diabetic rats, and that a COX2 inhibitor will have a protective effect on diabetic cognitive impairment. In this study, we investigated the protection of meloxicam on cognitive impairment in diabetic rats as well as the alterations of COX2, PGE2, and its downstream pathway.…”
Section: ■ Introductionmentioning
confidence: 99%
“…24,25 Our previous study showed that the four different receptor subtypes of PGE2 participated in brain injury caused by aluminum overload. 26 On the basis of these reports, we hypothesized that COX2 and its downstream signaling pathway may participate in cognitive impairment in diabetic rats, and that a COX2 inhibitor will have a protective effect on diabetic cognitive impairment. In this study, we investigated the protection of meloxicam on cognitive impairment in diabetic rats as well as the alterations of COX2, PGE2, and its downstream pathway.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Liang reported that EP4 agonist reduces infarct volume and ameliorates long term behavioral deficits after ischemia, whereas genetic inactivation of EP4 worsened stroke outcome [ 69 ]. Contrary to the studies, our previous study demonstrated that PGES-PGE2-EP4 signaling pathway disorders might related to cerebral injury and neuronal degeneration rats caused by chronic aluminum overload [ 66 ]. In present study, the expression EP4 mRNA in aluminum overload group significantly increased compared with control group.…”
Section: Discussionmentioning
confidence: 82%
“…McCullough reported that activation of EP2 receptor can protect against toxicity in ischemia, hypoxia and excitotoxic models in a cAMP dependent manner, while genetic deletion of EP2 receptor can exacerbate infarction of cerebral cortex and subcortical structures [ 65 ]. Our previous study demonstrated that PGES-PGE2-EP2 signaling pathway disorders might have a vital role in cerebral injury and neuronal degeneration rats caused by chronic aluminum overload, while the mechanism of which is still unknown [ 66 ]. In the present study, EP2 was highly expressed in aluminum overload primary hippocampal neurons, whereas treatment with EP2 antagonist (AH6809) aggravated the aluminum-overload damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proceed as follows: dewaxing in xylen, hydration in alcohols, HE staining, dehydration in alcohols, transparent in xylen and mounting with neutral resins. Ten consecutive fields were selected randomly from the hippocampal and cortical neurons, and the morphological changes were observed under an optical microscope (Olympus, Japan) at 400× magnification ( Guo et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%